How do consumers in Portugal perceive language learning APPS, and what are their preferred attributes? - Vilariça, Isabel (2025)
The rise of mobile technology has transformed how individuals learn new languages, with language learning (LL) apps offering flexible, user-centered alternatives to traditional methods. This study investigates how Portuguese consumers perceive LL apps, namely Duolingo, Babbel, Falou, and Buddy.ai, identifying preferred features. Marketing research techniques, including perceptual mapping, conjoint analysis, and qualitative interviews, reveal a trade off in consumers' minds between effectiveness and enjoyment, along with strong price sensitivity favoring freemium models. Duolingo dominates the market despite user dissatisfaction, driven by strong brand loyalty and platform's convenience. This research proposes launching a new entrant leveraging these insights to compete effectively.